A butterfly that thinks itself a bird: the identity of customary courts in Nigeria. Issue 3 (2nd September 2019) - Diala, Anthony C.
Abstract: Over the past 600 years, African states have been subjected to powerful influences of globalisation such as the slave trade, colonialism, transcultural exchange, and the law and development movement. These influences, which reflect in transplanted European laws masquerading as state laws, are steadily eroding the identity of indigenous African laws. So, to what extent do customary courts in Nigeria reflect indigenous law identity? This unexplored question is significant for scholarly and policy perceptions of legal pluralism in post-colonial states. These perceptions tend to favour conflict of laws, rather than the dialogue occurring between indigenous laws and state laws in intersectional social fields. Informed by case analysis, interviews, and archival searches, this article presents Nigerian customary courts as Anglicised courts pretending to be indigenous courts. It argues that customary courts illustrate indigenous law's adaptation to socioeconomic changes. In exposing state laws as a key component of these changes, the article highlights the ways customary court actors engender behavioural changes that reveal the adaptive nature of normative interaction in post-colonial societies. It suggests that the adaptive interface of state laws and indigenous laws offers a theoretical platform for legal integration in sub-Saharan Africa.